Voyage on the great Titanic : the diary of Margaret Ann Brady, R.M.S. Titanic, 1912 - White, Ellen Emerson (New York : Scholastic, 1998)
In her diary in 1912, thirteen-year-old Margaret Ann describes how she leaves her lonely life in a London orphanage to become a companion to a wealthy American woman, sails on the Titanic, and experiences its sinking.
Keywords: Titanic (Steamship) -- Juvenile fiction; Titanic (Steamship) -- Fiction; Shipwrecks -- Fiction; Ocean liners -- Fiction; Orphans -- Fiction; Diaries -- Fiction; London (England) -- Fiction